Antioxidants did not prevent muscle damage in response to an ultramarathon run - Mastaloudis, A.; Traber, M. G.; Carstensen, K.; Widrick, J. J. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study was conducted to determine if 6 wk of supplementation with vitamins E and C could alleviate exercise-induced muscle damage. We studied 22 runners during a 50-km ultramarathon.